Ground work on groundnut disease - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Groundnut Rosette Virus Disease (GRVD) is the most serious disease of groundnuts in Africa. In bad years it can wipe out a crop. But there is good news from the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT). A...